Austerity the demolition of the welfare state and the rise of the zombie economy - Mendoza, Kerry Anne. (Oxford New Internationalist, 2015)
For the last five years, Britain has been under the hammer of ?Austerity?. In its name, wages have been frozen, benefits have been slashed and public spending squeezed. The pain of a financial crisis caused by bankers and speculators has been borne by ordinary people all over the country ? and by the poor and disabled most of all.
Includes bibliographical references.
Keywords: Great Britain -- Economic conditions -- 21st century; Great Britain -- Social conditions -- 21st century